2017
DOI: 10.5534/wjmh.17011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Holmium Laser Enucleation of the Prostate in Patients with a Small Prostate (≤30 mL)

Abstract: PurposeWe investigated the effects of holmium laser enucleation of the prostate (HoLEP) in patients with a small prostate (≤30 mL) in whom medical treatment was ineffective.Materials and MethodsData from 132 patients who underwent HoLEP by a single surgeon between 2012 and 2015 were retrospectively analyzed. All patients received benign prostatic hyperplasia medication for at least 6 months before surgery. The patients were divided into 2 groups according to prostate size: group 1, ≤30 mL (n=30); and group 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…In previous studies on such complications, no differences were reported in terms of urgency, dysuria, and transient incontinence between the TURP and HoLEP groups [7]. In another study, 5 cases of blood transfusion requirement and 38 cases of transient incontinence were noted among 459 patients who underwent HoLEP [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies on such complications, no differences were reported in terms of urgency, dysuria, and transient incontinence between the TURP and HoLEP groups [7]. In another study, 5 cases of blood transfusion requirement and 38 cases of transient incontinence were noted among 459 patients who underwent HoLEP [19].…”
Section: Discussionmentioning
confidence: 98%
“…HoLEP is a unique method that can be performed independent of the prostate size. Although there are many studies on the use of HoLEP in large prostates [2][3][4]6], studies on it use in small prostates are limited [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although HoLEP is addressed as a surgical treatment option of small prostate flow chart in AUA guidelines, it is still stayed behind transurethral incision of the prostate and transurethral resection of the prostate (TURP) for small prostate treatment options in EAU guidelines (Foster et al., 2018; Gratzke et al., 2015). The effect of prostate size on the outcome of HoLEP surgery has been studied in the literature; most of the published papers compared the large prostates above 80 or 100 ml (Gazel et al., 2019; Glybochko et al., 2017; Hettiarachchi et al., 2002; Jones et al., 2016; Kuntz et al., 2008; Zhang et al., 2020) and some compared small prostates below 40 or 30 ml (Kim et al., 2016, 2019; Park et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…BNCs and capsular perforations are of concern in these patients due to high energy delivered to the tissue creating scarring of the bladder neck [6], [15]. There have only been a few studies evaluating the efficacy of BPH surgery in patients with small volume prostates [16], [17], [18]. However, due to the paucity of literature addressing the 180 W PVP in small prostates [16], [17], [18], it remains unclear the effectiveness of 180 W PVP for this cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…There have only been a few studies evaluating the efficacy of BPH surgery in patients with small volume prostates [16], [17], [18]. However, due to the paucity of literature addressing the 180 W PVP in small prostates [16], [17], [18], it remains unclear the effectiveness of 180 W PVP for this cohort of patients. We sought to assess the safety and efficacy of the 180 W XPS-GreenLight laser in patients with a BPH volume ≤40 mL.…”
Section: Introductionmentioning
confidence: 99%